Pertanggungjawaban Pengurus Bank BUMN dalam Pemberian Kredit oleh Bank BUMN Periode 2001-2010 - Dodi Suhartono Abdulkadir (Universitas Nasional, 2022)
This research is based on the phenomenon of a shift from civil law to criminal law, resulting in criminalization efforts against corporate management which are limited liability companies for the occurrence of credit applications which are categorized as bad loans even though they have material rights as collateral which give birth to negative implications for business development in general and banking development in particular. By using the normative juridical method, this study aims to further examine the accountability of BUMN bank management in providing credit by BUMN banks for the period 2001-2010. Based on the results of the study, it is concluded that the responsibility of BUMN bank management in providing credit by BUMN Banks for the 2001-2010 period is civil liability as long as in its implementation the principles of sound corporate management have been applied (Good Corporate Governance), business judgment rules dan fiduciary duty. Penelitian ini dilatarbelakangi oleh fenomena pergeseran dari hukum perdata ke hukum pidana, sehingga terjadi upaya kriminalisasi terhadap pengurus perseroan yang berbentuk perseroan terbatas atas terjadinya permohonan kredit yang dikategorikan kredit macet meskipun mempunyai hak kebendaan sebagai agunan yang melahirkan implikasi negatif untuk pengembangan usaha pada umumnya dan pengembangan perbankan pada khususnya. Dengan menggunakan metode yuridis normatif, penelitian ini bertujuan untuk mengkaji lebih lanjut pertanggungjawaban manajemen bank BUMN dalam pemberian kredit oleh bank BUMN periode 2001-2010. Berdasarkan hasil penelitian disimpulkan bahwa tanggung jawab pengurus bank BUMN dalam pemberian kredit oleh Bank BUMN periode 2001-2010 adalah perdata sepanjang dalam pelaksanaannya telah diterapkan prinsip-prinsip pengelolaan perusahaan yang sehat (Good Corporate Governance), aturan penilaian bisnis dan kewajiban fidusia.